THERMO-SENSOR DIAGNOSTICS OF AK9CH ALLOY SOLIDIFICATION PROCESS IN THE DEVELOPMENT OF TECHNOLOGY FOR DEFECT-FREE CASTINGS - P. E. Lushchik (Литьë и металлургия)
This paper shows the practical application of algorithm for calculating the volume fraction of solids for the computer simulation of aluminum castings technology